Educate to Activate: A Serial Mediation Approach to Entrepreneurial Intentions among Vocational Students - Dede Kurnia; Azizah Fauziyah; Nizza Nadya Rachmani (FKIP UNIVERSITAS PAKUAN, 2025)
This study explores how entrepreneurial education shapes students' entrepreneurial intentions through psychological mechanisms. Specifically, it examines the mediating roles of subjective norms, personal attitudes, and perceived behavioral control in this relationship. A survey was conducted involving 366 vocational high school students in Tasikmalaya. The collected data were analyzed using the Serial Multiple Mediation (SMM) model with Hayes’ PROCESS macro to test the proposed framework. The results indicate that entrepreneurial education does not have a direct effect on students' entrepreneurial intentions. Instead, its impact is entirely mediated by subjective norms, personal attitudes, and perceived behavioral control, each of which shows a significant positive influence on entrepreneurial intentions. These findings highlight the importance of psychological factors in translating entrepreneurial education into actionable intentions, suggesting that enhancing these factors could improve the effectiveness of entrepreneurship programs.